Peningkatan Kapasitas Mesin Rubber Sheet Calendar Menggunakan Discrete Event Simulation: Studi Kasus di Industri Pengolahan Karet - Herdiana, Mochamad Rafi; Elfantoro, Indra; Dewi, Yulida Intani; Kurniawan, Indra (Study Program of Industrial Engineering, Udayana University, 2025)
Increasing production capacity is one of the key strategies to maintain the competitiveness of tire companies in an increasingly dynamic and competitive market. One of the critical machines in the tire production process is the Rubber Sheet Calender, which currently has a capacity of only 2700 Tires Per Day (TPD). However, based on the sales forecast for 2025, the required production capacity is expected to reach 3000 TPD. This study aims to analyze and enhance the capacity of the Rubber Sheet Calender machine using the Discrete Event Simulation (DES) approach. Data were collected through direct observation, time studies, and interviews with machine operators and production supervisors. A simulation model was developed to represent the actual condition (as-is), and improvement scenarios were tested, including adding labor, increasing buffer capacity, and reducing setup time. The simulation results show that a combination of improvements can significantly increase throughput by increasing machine speed from 4.65 to 6.31 (a 36% increase) and raising production capacity from 3360 to 4962 (a 59% increase). Thus, the improvement recommendations using DES have proven to be an effective decision-support tool for enhancing production capacity.